Determination of optimum conditions of planing for amarillón fron plantation in Costa Rica, Terminalia amazonia (J.F. Gmel) Exell. - Serrano-Montero, José Rafael (2012)
Terminalia amazonia (J.F. Gmel.) Exell has shown excellent growing rates in the Perez Zeledón zone. At this moment, industrialization of this timber is been developed, therefore it is necessary to know more about their optimum condition of planing. Testing procedures of the American Society for Testing and Materials ASTM-D-1666-87, with modifications proposed for tests of tropical woods were used. Lumber material was conditioned to 12 % moisture content. Machining characteristics of planing in this study included; the percentage of area free of defects, torn or chipped grain, raised grain and fuzzy grain. According to the results, lumber from this species demonstrated good planing characteristics, for example, the percentage of area free of defects was above 90 % for the two cutting angles (10o and 30o ) applied, in combination with four feed speeds (6, 9, 12 and 15 m/min.) and three cutting planes; radial, tangential and combined one (radial and tangential). It was determined a cutting angle (rake angle) of 10o and a feed speed of 9 m/min., as the optimum conditions for planning.